Quick start guide to Oracle Fusion development [ Oracle jDeveloper and Oracle ADF - Ronald, Grant (McGraw-Hill, 2011)
"Written by a Group Product Manager at Oracle, this OraclePress guide gets you up and running quickly with your first Oracle Fusion applications. Quick Start Guide to Oracle Fusion Development provides only the essential information you need to build applications in a matter of hours. Rapidly learn the building blocks and functionalityyou'll use most of the time. The progression of topics closely matches the application building process, taking you through a typical developer scenario from start to completion."